Toxicity Of Some Plant Powder Against Life Stages Of Rhizopertha Dominica (F.) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Toxicity of some important indigenous plant powder (Nigella sativa Linn.,Murrayapaniculata Linn., Jatrophacurcas Linn., Eucalyptus camaldulensisDehn., DaturametelLinn., and Vitexnegundo Linn.) were used against different life stages of lesser grainborer, Rhizoperthadominica (Fabricius). Among them seed powder of N. sativa provedto be the most effective as toxicant. The results revealed to reduce the egg mortality,larval mortality and adult mortality of R. dominica significantly (P M. paniculata> J. curcas> E.camaldulensis> D. metel> V. negundo. All the plant powders were found to be effectivefor controlling stored product insect pests especially R. dominica and eco-friendlybiopesticides.Asiat. Soc. Bangladesh, Sci. 41(1): 115-122, June 2015